2000
DOI: 10.1161/01.cir.102.6.617
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plaque Components With Intravascular Ultrasound Elastography in Human Femoral and Coronary Arteries In Vitro

Abstract: Different strain values are found between fibrous, fibro-fatty, and fatty plaque components, indicating the potential of intravascular elastography to distinguish different plaque morphologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
187
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(192 citation statements)
references
References 23 publications
2
187
0
3
Order By: Relevance
“…The example shown in Fig. 5A illustrates that IMT locally even increases during the cardiac cycle (⌬IMT Ͼ 0), suggesting possible displacement of wall mass from adjacent parts of the arterial wall to the focal site (8,10). Other subjects with positive inhomogeneities showed similar features.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The example shown in Fig. 5A illustrates that IMT locally even increases during the cardiac cycle (⌬IMT Ͼ 0), suggesting possible displacement of wall mass from adjacent parts of the arterial wall to the focal site (8,10). Other subjects with positive inhomogeneities showed similar features.…”
Section: Discussionmentioning
confidence: 82%
“…Although ⌬IMT is not the same as elasticity, it can be envisaged that it will change when artery wall properties are altered (8,10). Intrasubject comparison of spatial with temporal variance in ⌬IMT showed inhomogeneities in a surprisingly large number of subjects (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced mathematical algorithms including radiofrequency analysis (RFA) and elastography allow a more detailed analysis 96,97 . IVUS-derived RFA (virtual histology, VH-IVUS) displays the reconstructed data as a color coded tissue map of plaque composition based on validation to histology [98][99][100] .…”
Section: Plaque Composition With Ivusmentioning
confidence: 99%
“…8 Preliminary experiments revealed that it is feasible to discriminate between fatty, fatty fibrous, and fibrous material with this technique. 9 The structure and the composition of the vessel change with age, hypertension, diabetes mellitus, and many other factors. 10 Because composition of the vessel wall affects the mechanical properties of a vessel, the analysis of mechanical behavior of the vessel wall may enhance our understanding of the pathophysiology of atherosclerotic disease.…”
mentioning
confidence: 99%